Musculoskeletal disorders (MSDs) in dancers and former dancers participating in the largest dance festival in the world - Grego Muniz de Araújo, L.; Luiz Monteiro, H.; Marcelo Pastre, C. (Science & Sports, 2013)
Objective: To verify the presence of musculoskeletal disorders (MSD) in dancers and former dancers participating in the 27th Joinville Dance Festival. Material and methods: The research was conducted at the 27th Joinville Dance Festival in Santa Catarina, Brazil, with 173 participants in the competition, where 139 were dancers and 34 were former dancers with at least ten years of practice. In order to obtain information related to MSDs, dancers answered a specific questionnaire. Results: The study group consisted of adults (28 ± 9 years) with body mass index within the normal range (21.3 ± 2.3) with high weekly training time (955.7 ± 837.2) and featuring long-time experience in dancing (18 ± 7 years). The lumbar spine and knees were the most affected by MSDs. The pain of high intensity was the symptom that most often appeared in reports among survey participants. Conclusion: It is important to have deeper knowledge of the prevalence of pain among professional dancers, the factors associated with pain conditions and its impact on everyday life in order to plan new forms of prevention and plan new forms of prevention and treatment within a multidisciplinary approach.